Small great things : a novel - Picoult, Jodi, 1966- (New York : Ballantine Books, an imprint ofRandom House, a division of Penguin Random House LLC, 2016)
A woman and her husband admitted to a hospital to have a baby requests that their nurse be reassigned - they are white supremacists and don't want Ruth, who is black, to touch their baby. The hospital complies, but the baby later goes into cardiac distress when Ruth is on duty. She hesitates before rushing in to perform CPR. When her indecision ends in tragedy, Ruth finds herself on trial, represented by a white public defender who warns against bringing race into a courtroom. As the two come to develop a truer understanding of each other's lives, they begin to doubt the beliefs they each hold most dear.
Includes bibliographical references.
Keywords: African American nurses -- Fiction; Criminal defense lawyers -- Fiction; Race relations -- Fiction; Racism -- Fiction